Productivity, competition behaviour and weed dynamics of various row proportions of maize (Zea mays)-legumes intercropping in Arunachal Pradesh - CHOUDHARY, V K; DIXIT, ANIL; KUMAR, P SURESH (The Indian Journal of Agricultural Sciences, 2014)
Intercropping is the simultaneous cultivation of more than one crop species on the same piece of land and is regulated as the practical application of basic ecological principles such as diversity, competition and facilitation. Farmers of the region sow many crops in a piece of land, without following any row proportion geometrics and hence crop productivity is considerably low. A research was carried out to assess the feasibility of raising intercrops in association with maize (Zea mays L.) at ICAR Research Complex for NEH Region, Basar during 2010 and 2011. The results indicated that biomass accumulation was the highest with 1:1 than in the 1:5 row proportions. Leaf area index of maize with intercrop was the highest with 1:5 row proportions. The maize grain yield was obtained relatively higher with solitary maize followed by 1:2 of maize-soybean [Glycine max (L.) Merr.]. Maize equivalent yield was 55.5% higher with 1:5 of maize-groundnut (Arachis hypogaea L.) over the solitary maize, consequently, production efficiency was remarkably improved by 48.9% with 1:5 of maize-groundnut. Land equivalent ratio, area time equivalent ratio and monetory advantage index were favourable for the intercropping implying their intrinsic advantage over solitary planting. Weed density and dry biomass were lower with 1:5 row proportions which resulted in higher weed smothering efficiency.